Perkembangan Pondok Pesantren Al-Musyarrofah di Kabupaten Cianjur Tahun 1975-2014 - Widinia Dinda Ayuningtyas; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The paper is entitled “The Development of Pondok Pesantren Al-Musyarrofah in Cianjur (1975-2014). The researcher’s interest about Al-Musyarrofah based on cohesiveness between traditional pesantren with formal education that develops so rapidly from increasing of santri every year, in addition the application the curriculum or method of Kulliyatul Mu’allimin wal Mu’allimat Al-Islamiyah and as well as santri of Al-Musyarrofah who come from all regions of Indonesia. As the main problem discussed in this paper is how the development of Pondok Pesantren Al-Musyarrofah in Cianjur (1975-2014)?. And then the main problem is divided into four research questions, namely: how the background establishment of Al-Musyarrofah?; how is the condition of Al-Musyarrofah under KH. Wildan Affandi’s leadership; how the development of educational institutions contained in Al-Musyarrofah?; what are the driving and inhibiting factors in development of Al-Musyarrofah?. The method used in this paper is the historical method, use the following steps: heuristic, external and internal critics, sources interpretation and historiography which includes a general description, the background of the establishment of pondok pesantren, the condition of Al-Musyarrofah under KH. Wildan Affandi’s leadership, the development of educational institutions contained in Al-Musyarrofah, the driving and inhibiting factors in development of Al-Musyarrofah. Referring to the results of the paper obtained several conclusions. Al-Musyarrofah was founded in 1833 by Syeikh Tb. Abdullah Umar Syarifuddin. The leadership of pesantren has been replaced by six generations, modernization of Al-Musyarrofah occurred in 2008 by establishing integrated Islamic Junior High School. Al-Musyarrofah doesn’t accept santri kalong, but only accept santri mukim.